Double maternal stigma : single, mad mothers in Japanese maternal horror - Nur Syahirah Binte Suradi (2017)
In Japanese maternal horror films, motherhood becomes a visually horrifying spectacle. Monstrous and abject representations of motherhood do not necessarily rely on monstrous depictions of the mothers themselves. The horror of motherhood also lies in the destructive mother-child relationship as it reveals the potentially devastating effects maternal failure may have on a child. While female yūrei, or spirits, from Japanese folklore depict physical monstrosity, monstrosity also lies in the mother’s inability to fulfil her maternal role. Maternal mental illness and single or divorced mothers become associated with monstrosity and maternal failure. This thesis will argue that monstrous and abject representations of motherhood and the mother-child relationship in Japanese maternal horror actually propagates a double layer of maternal stigma and reveals underlying cultural anxieties towards these stigmatised mothers.